An in Situ Atlas of Mitochondrial DNA in Mammalian Tissues Reveals High Content in Stem and Proliferative Compartments - Chen, Jiayu; Zheng, Qizhi; Peiffer, Lauren B.; Hicks, Jessica L.; Haffner, Michael C.; Rosenberg, Avi Z.; Levi, Moshe; Wang, Xiaoxin X.; Ozbek, Busra; Baena-Del Valle, Javier; Yegnasubramanian, Srinivasan; De Marzo, Angelo M. (The American journal of pathology, 2020)
Mitochondria regulate ATP production, metabolism, and cell death. Alterations in mitochondrial DNA (mtDNA) sequence and copy number are implicated in aging and organ dysfunction in diverse inherited and sporadic diseases. Because most measurements of mtDNA use homogenates of complex tissues, little is known about cell-type–specific mtDNA copy number heterogeneity in normal physiology, aging, and disease. Thus, the precise cell types whose loss of mitochondrial activity and altered mtDNA copy number that result in organ dysfunction in aging and disease have often not been clarified. Here, an in situ hybridization approach to generate a single-cell–resolution atlas of mtDNA content in mammalian tissues was validated. In hierarchically organized self-renewing tissues, higher levels of mtDNA were observed in stem/proliferative compartments compared with differentiated compartments. Striking zonal patterns of mtDNA levels in the liver reflected the known oxygen tension gradient. In the kidney, proximal and distal tubules had markedly higher mtDNA levels compared with cells within glomeruli and collecting duct epithelial cells. In mice, decreased mtDNA levels were visualized in renal tubules as a function of aging, which was prevented by calorie restriction. This study provides a novel approach for quantifying species- and cell-type–specific mtDNA copy number and dynamics in any normal or diseased tissue that can be used for monitoring the effects of interventions in animal and human studies.